2019
DOI: 10.18488/journal.aefr.2019.94.450.460
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Efficacy of Foreign Aid and Grants in Poverty Reduction in Nigeria

Abstract: This study re-examines the efficacy of foreign aid and grants on poverty reduction in Nigeria using time series data covering the period of 1999 to 2017. To perform the inquiry, the paper focus on disaggregated data for the analysis of foreign aid and grants, that is, technical cooperation grants (TCG), official development assistance (ODA) and other grants. Grounded on the Great Big Push theoretical framework, the study tested the marginal effect of TCG, ODA and other grants on poverty incidence in Nigeria us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The framework of analysis adopted in this study is the Big Push Theory which argues that to escape the poverty trap and take-off into national development requires a significant inflow of aggregate aid (such as grants and concessional loans) in social and productive sectors which will result in growth across all sectors of poor societies (Shitile & Sule, 2019). The major proponent of this theory was Paul Narcyz Rosenstein-Rodan.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The framework of analysis adopted in this study is the Big Push Theory which argues that to escape the poverty trap and take-off into national development requires a significant inflow of aggregate aid (such as grants and concessional loans) in social and productive sectors which will result in growth across all sectors of poor societies (Shitile & Sule, 2019). The major proponent of this theory was Paul Narcyz Rosenstein-Rodan.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Their analysis revealed that social aid such as education, health and water and sanitation spending significantly and directly benefits the poorest in the society and economic aid on the other hand, like transportation, energy and communication and financial infrastructure spending increases the income of the poor through growth (Hirano and Otsubo, 2014). Notwithstanding, many scholars concluded that foreign aid or official development assistance (ODA) has direct or indirect influence on reducing Proceedings of the International Conference on Industrial Engineering and Operations Management Istanbul, Turkey, March 7-10, 2022 poverty; others state that it does not affect poverty reduction strategy for example, Briggs and Briggs (2015); Appiahkonadu et al (2016); Ugwuanyi, Uche Boniface, Ezeaku, Hillary Chijindu (2017); Chikwede, (2017) ;Muftau, (2018); Pedro Gil, (2018) and Shitile and Abubakar (2019).…”
Section: Relationship Between Foreign Aid and Poverty Reductionmentioning
confidence: 99%